2002
DOI: 10.2741/quintela
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-induced alterations in serum immunoglobulin E (IgE) levels in human subjects

Abstract: The association of alcohol intake with total serum IgE concentrations in humans is discussed in the present review. The possible relationship of regular alcohol intake with both the risk of allergic sensitization and serum allergen-specific IgE values is also reviewed. Several studies consistently show that total serum IgE concentrations are increased in alcoholics when compared with healthy controls. Total serum IgE levels decrease after ethanol abstinence in alcoholics. Total serum IgE is increased in modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Excessive and even moderate consumption of alcohol increases levels of serum total IgE, as reviewed by González‐Quintela et al [24]. Recently, population‐based studies have confirmed this effect [25, 26].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Excessive and even moderate consumption of alcohol increases levels of serum total IgE, as reviewed by González‐Quintela et al [24]. Recently, population‐based studies have confirmed this effect [25, 26].…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with the notion that the effect of alcohol on the fetal immune system is transient and attenuates after ceased exposure to alcohol at birth where the maternal and fetal circulations are separated. The alcohol‐mediated increase in serum IgE in alcoholics also appears to be transient, since serum IgE decreases within weeks from the time of alcohol abstinence [24]. Accordingly, the increased levels of histamine in the blood of the newborn offspring of ethanol‐fed rats returned to control values after birth [19].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol ingestion has been associated with elevated IgE levels [91]. Certain forms of nephritides demonstrate IgE elevation [92].…”
Section: Immune Dysregulation Associated With High Ige Levelsmentioning
confidence: 99%
“…Alcohol consumption by the mother during pregnancy is associated with higher total IgE levels in cord blood [76]. Alcohol consumption in adults is also a risk factor for elevated specific IgE levels against food antigens [77,78].…”
Section: Part 2: Prevention Of Asthma and Allergies In Early Lifementioning
confidence: 99%
“…Moreover, alcohol consumption has been shown to induce higher IgE levels against aeroallergens in atopic patients [76]. …”
Section: Part 2: Prevention Of Asthma and Allergies In Early Lifementioning
confidence: 99%